Underwater augmented reality for improving the diving experience in submerged archaeological sites. (15th October 2019) - Bruno, Fabio; Barbieri, Loris; Mangeruga, Marino; Cozza, Marco; Lagudi, Antonio; Čejka, Jan; Liarokapis, Fotis; Skarlatos, Dimitrios
Abstract: The Mediterranean Sea has a vast maritime heritage which exploitation is made difficult because of the many limitations imposed by the submerged environment. Archaeological diving tours, in fact, suffer from the impossibility to provide underwater an exhaustive explanation of the submerged remains. Furthermore, low visibility conditions, due to water turbidity and biological colonization, sometimes make very confusing for tourists to find their way around in the underwater archaeological site. To this end, the paper investigates the feasibility and potentials of the underwater Augmented Reality (UWAR) technologies developed in the iMARECulture project for improving the experience of the divers that visit the Underwater Archaeological Park of Baiae (Naples). In particular, the paper presents two UWAR technologies that adopt hybrid tracking techniques to perform an augmented visualization of the actual conditions and of a hypothetical 3D reconstruction of the archaeological remains as appeared in the past. The first one integrates a marker-based tracking with inertial sensors, while the second one adopts a markerless approach that integrates acoustic localization and visual-inertial odometry. The experimentations show that the proposed UWAR technologies could contribute to have a better comprehension of the underwater site and its archaeological remains. Highlights: UWAR to improve the diving experience of the Underwater Cultural Heritage. UWAR based on a marker-based tracking with inertial sensors. Markerless UWAR that integrates acoustic localization and visual inertial odometry.